Herbal Juice - Japital, Ilerosan; Verus, Venessa Vesselisa; Anit, Nelly; Francis, Joannes; Brahin, Nur Azatul Wada (2016)
Our business is about herbal juice that incorporate two main ingredients, pineapple and coriander. Our business start to operate on 28th august 2016. We are selling our product for people who love themselves and concern about their health. Our business operates at Taman Canggih, Lorong Canggih 1, Jalan Tuaran By Pass, Kampung Darat, 88450, Kota Kinabalu, Sabah, Malaysia. We chose this location because we believe that our place is strategic enough, our building is near to the main road, more over our business is located near to the housing that was only 400 m away. This will give more benefits and potential to our business. We are confident that our product will be able to compete with other product such as Tropicana Twister, Yeo's, Lipton, F&N seasons, and Oishi. It is because our product has its own specialties because this product has not been commercialized yet by other company and we believe that we are the first company in Malaysia that releasing this new product. When people think of coriander, people will think of it in soup but in our product, we try to make a twist by changing it into drink instead.